2020
DOI: 10.46328/ijte.v3i2.22
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Skills in Asynchronous Discussion Forums: A Case Study

Abstract: This study investigated critical thinking indicators of students’ postings on the asynchronous online discussion forums on the learning management system (LMS) at Arab Open University (AOU), Jordan. The models used to diagnose nineteen students’ postings were Garrisons’ (2001) thinking skills and Newman (1995). Results revealed that participants’ postings reflected the critical thinking indicators proposed by Newman like relevance and importance, but students need to enhance skills like justification, and crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 21 publications
(27 reference statements)
2
36
0
3
Order By: Relevance
“…It is important to understand the impact of distance learning on the effects of education and the social consequences of maintaining this type of education. Many researchers have extensively studied the impact of distance learning on education and have found that distance education has a number of benefits such as ensuring the continuity of education [17,18], ensuring a lifelong learning [19,20], and reducing the high costs associated with traditional education [21]. Limitations such as teaching methods, scheduling, and time have existed since the teacher and the learner were located in different places [22,23].…”
Section: The Impact Of Covid-19 Pandemic On Educationmentioning
confidence: 99%
“…It is important to understand the impact of distance learning on the effects of education and the social consequences of maintaining this type of education. Many researchers have extensively studied the impact of distance learning on education and have found that distance education has a number of benefits such as ensuring the continuity of education [17,18], ensuring a lifelong learning [19,20], and reducing the high costs associated with traditional education [21]. Limitations such as teaching methods, scheduling, and time have existed since the teacher and the learner were located in different places [22,23].…”
Section: The Impact Of Covid-19 Pandemic On Educationmentioning
confidence: 99%
“…There are many variables that make a difference in the learning process in music teacher education. Factors such as student's knowledge, skills, abilities, learning competencies, learning strategies and styles, teaching-learning environment, tools, materials and motivation can be listed (Ak, 2018;Boon, 2020;Bulut, 2021;Al-Husban, 2020;Gonzales et al, 2017;Atilgan & Tukel, 2021;Grohs et al, 2018;Hazar, Akkutay, & Keser, 2021;Hewit, 2001;Kaleli, 2020Kaleli, , 2021Kara, 2020b;Kasimoglu, 2021;Koyuncuoğlu, 2021;Kurnaz, 2007;McPherson, 2005;Matthews & Kitsantas, 2012;Mentiş Köksoy & Aydıner Uygun, 2018;Syafii, Kusnawan, & Syukroni, 2020). One of these variables is self-regulatory skills and International Journal on Social and Education Sciences (IJonSES) 549 strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca e-öğrenme ve çevrim içi öğrenme olarak da ifade edilen uzaktan eğitim kavramı, eğitim öğretim faaliyetleri sürdürülürken öğretmen ve öğrencilerin aynı ortamda fiziki olarak bulunmamasını (Kaplan ve Haenlein, 2016) ve bireylerin iletişimini kolaylaştırmak adına farklı teknolojilerin kullanılmasını kapsayan eğitim biçimi olarak da karşımıza çıkmaktadır (Sutiah, Slamet, Shafqat ve Supriyono, 2020). Uzaktan eğitimin yaşam boyu öğrenme (Alharthi, 2020;Pambayun, Wirjawan, Wijaya, Untung ve Pratidhina, 2019;Serhan, 2019) sunmasına ek olarak eğitim maliyetlerini azaltması (Al-Husban, 2020;Baggaley, 2008;Hall ve Knox, 2009;Harrison ve Lee, 2018) eğitimin sürdürülebilirliğini sağlaması (Akinbadewa ve Sofowora, 2020;Bruder, 1989;Omiles, Dumlao, Rubio ve Ramirez, 2019;Seage ve Türegün, 2020) gibi faydaları bulunmaktadır. Ayrıca araştırmacılar uzaktan eğitimin teknik imkanlarına değinirken aynı zamanda pratik deneyimin çok az olması, öğrenci ve ebeveynlerin psikolojik hazırlığının olmaması gibi birtakım sorunlara da dikkat çekmektedirler (Yakovleva ve Koriakina, 2020).…”
Section: Introductionunclassified